An Enhanced Fuzzy Rule Based Protection Scheme for TCSC Compensated Double Circuit Transmission System. (4th March 2021) - Nale, Ruchita; Verma, Hari; Biswal, Monalisa
ABSTRACT: This paper introduces a fault detection and faulty phase selection technique for a double-circuit transmission line with thyristor-controlled series capacitor (TCSC). In a transmission system, the nonlinear operation of TCSC during switching modes distorted the voltage and current signals. The effect is more if the fault occurred at zero fault inception angle. An advanced protection approach to overcome these issues based on dynamic phasor estimation of current from local measurements is proposed in this work. The maximum transient component obtained from three phases is used as an index to accomplish the detection task. However, due to the nonlinear operation of different accessories connected to the controller unit such as metal oxide varistor (MOV) and thyristor circuit, identification of the exact faulty phase is still a challenge. To mitigate this issue, fuzzy decision-based rules are framed so that identification of exact faulty phases is possible. For validation, the method is tested on a 400-kV, 50-Hz power system model developed using EMTDC/PSCAD. Results obtained from simulation indicate that the method is reliable and a secure unit protection can be effectively provided to a double-circuit transmission system equipped with TCSC.